ChemInform Abstract: One‐Pot Chemoselective Synthesis of Arylated Benzo[h]quinolines. Issue 17 (April 2015) - Singh, Surjeet; Yadav, Pratik; Sahu, Satya Narayan; Sharone, Ashoke; Kumar, Brijesh; Ram, Vishnu Ji; Pratap, Ramendra
Abstract The reactions are performed under microwave irradiation as well as conventional heating with the latter delivering lower product yields.